Design and implementation of a synchronous buck DC–DC converter with incremental conductance MPPT for green hydrogen production via PEM electrolysis - Novan Akhiriyanto; Rizky Muhammad Afandi (National Research and Innovation Agency, 2025)
The integration of green hydrogen production systems with photovoltaic (PV) energy sources presents challenges due to voltage mismatches between commercial solar charge controllers and the required input of proton exchange membrane (PEM) electrolyzers. This study presents an experimental implementation of a maximum power point tracking (MPPT) module using the incremental conductance (INC) algorithm embedded in a parallel buck converter configuration. The objective is to supply a stable low-voltage, high-current input to a PEM electrolyzer from a solar-powered system. The system employs three parallel connected buck converters, each operating within a 3 V to 7 V range and capable of delivering up to 20 A and 60 W to 120 W per module. Combined, the converters manage a power range of 180 W to 360 W to match the electrolyzer’s requirements under variable irradiance. The MPPT algorithm actively adjusts duty cycles to maintain the PV panel’s output near its optimal power point, targeting 150 W to 210 W. Voltage, current, and power readings from both PV and converter sides are acquired in real time via PZEM-017 sensors. Testing was performed over a three-hour period during peak solar irradiance (10:40 AM–1:40 PM) to ensure observation within the maximum power window. The average output from the parallel buck converter was 4.36 V, 25.41 A, and 111.26 W, while the PV panel delivered 154.41 W. Real-world system efficiency ranged from 59.48 % to 70.04 %, with a peak potential of 72.05 %. These results confirm the viability of using a parallel buck converter controlled by INC MPPT to drive a PEM electrolyzer in green hydrogen applications. The findings also indicate opportunities to further enhance efficiency through system refinement and control optimization.